QUANTITATIVE ANALYSIS OF THE CONSUMPTION OF ANTIBACTERIALS PRESCRIBED IN THE AMBULATORY CARE AND REIMBURSED BY HII IN ALBANIA DURING 2011-2012 - Hoxha, Iris; Malaj, Admir; Malaj, Ledjan; Petrela, Elizana (European Scientific Journal, ESJ, 2014)
Background: Emphasis on the misuse of antibacterials in Albania and an increased sensibility on the antibacterial resistance have been reported in the grey literature lately. However, until now there are no consistent data on antibacterial use, its related misuse and antibacterial resistance, either other reports produced by health institutions. Objective: The objective of this study is to assess the trend of antibacterial utilization reimbursed by the Health Insurance Institute (HII) in the ambulatory care in Albania during the period 2011-2012. Materials and Methods: Data from the HII database for all the reimbursed and dispensed antibacterial in the ambulatory care were taken and the methodology of ATC/DDD for the study of antibacterial utilization was applied. Antibacterial grouped in ATC class were measured in defines daily doses (DDDs) and DDD/1000 inhabitant/day (DIDs) and then compared with the data of the European Surveillance of Antimicrobial Consumption Network (ESAC-Net) reports. Results:Results of the total consumption of antibacterials reimbursed by the HII measured during 2011 are (3.174 DIDs) and in 2012 (2.794 DIDs).The penicillin’s total consumption in 2011 are (1.604 DID) and in 2012 (1.306 DID). From 2011 to 2012 there are no significant differences in the total antibacterial consumption. However, an enhancement of the use of third generation of cephalosporin’s was distinguished within the class of cephalosporin’s during the year 2012 (0.038 DID) whereas in the year 2011 was (0.006 DID). Conclusions:The quantities of antibacterial reimbursed for HII covered population during 2011 and 2012 are lower than the average consumption of EU/EAA countries part of ESAC-Net project. However, cephalosporin’s and tetracycline’s quantities reimbursed and dispensed were similar with the relative data of some countries of EU/EAA countries part of the ESAC-Net project.